Considering factors that leads to sustainability of Small and Medium Enterprises in Ghana using PESTEL and theories of entrepreneurship as a measuring tool - Amoako, Seth; Boateng, Elvis (Technium Social Sciences Journal, 2022)
This study was intended to identify factors that lead to the sustainability of small and medium enterprises in Ghana using PESTEL and theories of entrepreneurship as a measuring tool and also made appropriate recommendations for readdressing. The study seeks to solve the problem of high pay to employees, a process that Small and Medium Enterprise face to access the loan and relatively high income to the employee. To enumerate various sources of funds available to SME’s in Ghana and to examine the different causes that contribute to the sustainability of small businesses in Ghana, consider the variables that lead to the collapse of new SME’s activities, to ascertain the impact of factors that contributes to the sustainability of SME’s in Ghana and to evaluate the PESTEL effect on SME’s in Ghana. Data were obtained through questionnaires from managers and entrepreneurs in Kumasi, Ghana. The sample was selected using quota, stratified and convenient sampling method. The data was analyzed using Statistical Package for Social Sciences (SPSS) in the form of tables. The researchers recommended that entrepreneurs or managers of Small Business should be expert in management in all spheres of business endeavor such as funds , human resource etc. for good management contribute to SME’s sustainability as well as dealing in good and quality goods or products for quality products contributes to SME’s sustainability